2003
DOI: 10.1046/j.1365-246x.2003.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

Holocene faulting and earthquake recurrence along the Serghaya branch of the Dead Sea fault system in Syria and Lebanon

Abstract: SUMMARY The Serghaya fault, located approximately along the Syrian–Lebanese border, is a prominent structure within the 200 km restraining bend in the left‐lateral Dead Sea fault system. This study documents palaeoseismic and geomorphic expressions of Holocene movements on the Serghaya fault based on trench excavations and radiocarbon dates. Trenches were excavated across and parallel to a 4.5 m fault scarp where Late Pleistocene sediments are faulted against Holocene alluvium and colluvium. Locally oblique sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 51 publications
(77 reference statements)
8
92
0
Order By: Relevance
“…Recent plate tectonic models have begun to suggest that the northern portion of this transform may be characterized as transpressional in nature. Recent studies have identified clear evidence of active tectonism along the DSFS, including paleoseismic indicators, for the main fault branches along the northern 500 km of the DSFS (i.e., north of approximately 32.5° N) [1][2][3][4][5]. Results of these studies firmly refute recent assertions that the northern DSFS and the strike-slip faults in the Bekaa Valley are presently inactive [6,7].…”
Section: Introductionmentioning
confidence: 92%
“…Recent plate tectonic models have begun to suggest that the northern portion of this transform may be characterized as transpressional in nature. Recent studies have identified clear evidence of active tectonism along the DSFS, including paleoseismic indicators, for the main fault branches along the northern 500 km of the DSFS (i.e., north of approximately 32.5° N) [1][2][3][4][5]. Results of these studies firmly refute recent assertions that the northern DSFS and the strike-slip faults in the Bekaa Valley are presently inactive [6,7].…”
Section: Introductionmentioning
confidence: 92%
“…It is one of the largest continental strike-slip faults in the world with more than 1000 km length and links the Red Sea seafloor-spreading center to the collision zone in SE Turkey. According to Butler et al (1997) and Gomez et al (2003) the DST can be subdivided into a southern and northern part, joined by a ~200 km long restraining bend (Lebanese segment). The DST has been active since the middle Miocene with a total displacement of 105 km in the south (Bartov et al, 1980;Eyal et al 1981;Garfunkel et al, 1981) and 70-80 km in the north (e.g.…”
Section: Regional Tectonic Settingmentioning
confidence: 99%
“…However, the analysis of the structural displacement has been proved controversial (Westaway, 2004;Mart et al, 2005). The estimated slip rate varies between 1 and 10 mm/a following different measurement techniques (field studies, GPS, e.g., Garfunkel et al, 1981;Klinger et al, 2000;Gomez et al, 2003;Pe'eri et al, 2002;Meghraoui et al, 2003).…”
Section: Regional Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent large earthquake is the double shock of March 16, 1956 (Ms = 4.8-5.1) which killed 136 people, destroyed 6000 houses and damaged 17,000 houses (Brazee and Cloud 1984;Khair et al 2000). Seismological trenches have shown that the return period of devastating earthquakes is about 1100 years along the Yammouneh Fault ), 1500-1750 years along the Mount Lebanon Thrust ) and ~1300 years along Serghaya Faults (Gomez et al 2003).…”
Section: Application To Beirutmentioning
confidence: 99%